Intercontinental trends in functional and phylogenetic structure of stream fish assemblages. Issue 24 (19th November 2019) - Bower, Luke M.; Winemiller, Kirk O.
Abstract: Understanding of community assembly has been improved by phylogenetic and trait‐based approaches, yet there is little consensus regarding the relative importance of alternative mechanisms and few studies have been done at large geographic and phylogenetic scales. Here, we use phylogenetic and trait dispersion approaches to determine the relative contribution of limiting similarity and environmental filtering to community assembly of stream fishes at an intercontinental scale. We sampled stream fishes from five zoogeographic regions. Analysis of traits associated with habitat use, feeding, or both resulted in more occurrences of trait underdispersion than overdispersion regardless of spatial scale or species pool. Our results suggest that environmental filtering and, to a lesser extent, species interactions were important mechanisms of community assembly for fishes inhabiting small, low‐gradient streams in all five regions. However, a large proportion of the trait dispersion values were no different from random. This suggests that stochastic factors or opposing assembly mechanisms also influenced stream fish assemblages and their trait dispersion patterns. Local assemblages tended to have lower functional diversity in microhabitats with high water velocity, shallow water depth, and homogeneous substrates lacking structural complexity, lending support for the stress‐dominance hypothesis. A high prevalence of functional underdispersion coupled with phylogenetic underdispersion could reflect phylogenetic niche conservatism and/or stabilizing selection. These findings imply that environmental filtering of stream fish assemblages is not only deterministic, but also influences assemblage structure in a fairly consistent manner worldwide. Abstract : Phylogenetic and trait dispersion approaches were used to determine the relative contribution of limiting similarity and environmental filtering to community assembly of stream fishes at an intercontinental scale. Our results suggest that environmental filtering and, to a lesser extent, species interactions were important mechanisms of community assembly for fishes inhabiting small, low‐gradient streams in all five regions. Local assemblages tended to have lower functional diversity in microhabitats with high stress, such as high‐water velocity, shallow water depth, and homogeneous substrates lacking structural complexity, lending support for the stress‐dominance hypothesis.